The differences in dividend payout ratio and market performance of companies that perform and do not perform real activities manipulation - Ana Ji'ah; Diyah Pujiati (STIE Perbanas Surabaya, 2013)
This research aims to provide empirical evidence of whether there is a difference in thedividend payout ratio and market performance of companies which perform and do notperform real activities manipulation in manufacturing companies listed in IndonesiaStock Exchange period 2009 2011. The model of real activities manipulation used isbased on Roychowdhury (2006). The Researcher uses regression model to determinethe value of abnormal operating cash flow. There are two hypotheses in this study, thefirst hypothesis testing uses Wilcoxon Mann Whitney Test to notice any differencein dividend payout ratio of companies that perform and do not perform real activitiesmanipulation. The second hypothesis test also uses Wilcoxon Mann Whitney Testto notice any difference in market performance of companies that perform and do notperform real activities manipulation. Based on the result of the analysis, many companiesperform real activities manipulation, so cash flow statement can be used as anindicator of whether the companies perform real activities manipulation. The firsthypothesis test result finds that there is no difference in dividend payout ratio of companiesthat manipulate and do not manipulate real activities. And the second hypothesistest result also finds that there is no difference in market performance of companiesthat manipulate and do not manipulate real activities.